Metode Pengajaran Kreatif Dalam Pendidikan Inklusi Di Tingkat Madrasah Ibtidaiyah - Saskia Azhara Putri; Firly Fadila Julita; Reni Ramita Sari; Dwi Yana Alidia Fitri; Wismanto Wismanto (Jurnal Insan Pendidikan dan Sosial Humaniora, 2024)
Education is the right of all citizens, regardless of origin, economic situation or physical condition. In the national education system, according to Law Number 20 of 2003, comprehensive education is guaranteed without any discrimination in any form. This is the importance of applying inclusive education in Madrasah Ibtidaiyah without exception. This article aims to describe creative learning strategies in inclusive education, especially at the basic level that not only emphasize motor skills but also the ability to interact with the social environment. This article uses a literature review method (Literature Review) by collecting data and sources related to a particular topic which is obtained from various sources such as journals, research reports, books (to e-books) and other library sources. The results showed that the creative learning strategies carried out by teachers can increase the use of goals, learning materials, media, methods, assessments, and learning environment by students. Learning strategies that can be applied to basic ABK students include remedial, deductive, inductive, heuristic, explanatory teaching strategies, classical, collaborative, and behavior changes.